COMMON MANIFESTATIONS OF SYSTEMIC LUPUS ERYTHEMATOSUS IN TERTIARY RHEUMATOLOGY CENTRE, PERAK - Wahinuddin S; Rashrina AR; Muhammad Faiz MS; Muhammad AA; Ong PS; Noraini MH; Sugathan S; Abdullah AC (Asian Journal of Medicine & Health Sciences, 2019)
Objective. A hospital-based cross-sectional descriptive study documenting the common clinical manifestations of systemic lupus erythematosus (SLE) in a tertiary rheumatology center in the state of Perak in Malaysia. Method. The 1997 American College of Rheumatology classification revised criteria and the 2012 Systemic Lupus International Collaborating Clinic criteria were used and all patients attending the rheumatology clinic at a tertiary referral centre were included. The demographics and other clinical information were retrieved from patients’ outpatient clinical records. Results. One-hundred SLE patients were included in this cross-sectional study, the majority of whom were of the Malay ethnic group (47%) followed by Chinese (41%) and Indians (12%). Almost 91% of the patients in our study were females. Mean age was 34.94 years (SD = 12.7; 95% confidence interval, 32.42 – 37.46), almost 79% were in the 20-50 years age group. Anti-nuclear antibody (ANA) was positive in 70% of patients while only 28% were positive for anti-double-stranded deoxyribonucleic antibody (dsDNA). Major clinical manifestations were hematological disorders (53%) followed by a malar rash (41%), photosensitivity (30%) and oral ulcers (27%). Conclusion. Clinical phenotypes, demographics of SLE patients in this study shows no significant difference across age, gender, and ethnic groups. The current data, though limited, shows a high frequency of hematological and mucocutaneous manifestation in these patients.